Computer Safety, Reliability, and Security 32nd International Conference, SAFECOMP 2013, Toulouse, France, September 14-27, 2013, Proceedings - Bitsch, Friedemann; Guiochet, Jérémie; Kaâniche, Mohamed; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 32nd International Conference on Computer Safety, Reliability, and Security, SAFECOMP 2013, held in Toulouse, France, in September 2013. The 20 revised full papers presented together with 5 practical experience reports were carefully reviewed and selected from more than 88 submissions. The papers are organized in topical sections on safety requirements and assurance, testing and verification, security, software reliability assessment, practical experience reports and tools, safety assurance in automotive, error control codes, dependable user interfaces, and hazard and failure mode analysis.
Safety Requirements and Assurance -- Testing and Verification -- Security -- Software Reliability Assessment -- Practical Experience Reports and Tools -- Safety Assurance in Automotive -- Error Control Codes -- Dependable User Interfaces.- Hazard and Failure Mode Analysis.
Keywords: Computer security; Computer communication systems; Software engineering; Algorithms; Computers and civilization; Special purpose computers; Systems and Data Security; Computer Communication Networks; Software Engineering; Algorithm Analysis and Problem Complexity; Computers and Society; Special Purpose and Application-Based Systems